2021
DOI: 10.3390/cancers13133363
|View full text |Cite
|
Sign up to set email alerts
|

Combination of the G-8 Screening Tool and Hand-Grip Strength to Predict Long-Term Overall Survival in Non-Small Cell Lung Cancer Patients Undergoing Stereotactic Body Radiotherapy

Abstract: The Geriatric 8 (G-8) is a known predictor of overall survival (OS) in older cancer patients, but is mainly based on nutritional aspects. This study aimed to assess if the G-8 combined with a hand-grip strength test (HGST) in patients with NSCLC treated with stereotactic body radiotherapy can predict long-term OS better than the G-8 alone. A total of 46 SBRT-treated patients with NSCLC of stage T1-T2N0M0 were included. Patients were divided into three groups: fit (normal G-8 and HGST), vulnerable (abnormal G-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…En omfattende geriatrisk vurdering (CGA) spiller en vigtig rolle i etableringen af en individuelt tilpasset behandlingsplan for den aeldre patient med kraeft [22]. Flere studier har vist, at størstedelen af aeldre patienter, der modtager strålebehandling, er skrøbelige, men betydningen af CGA hos denne patientgruppe er fortsat ikke fuldstaendigt afklaret [23,24]. En CGA kan formentlig bidrage til individuelle hensyn til gennemførelse af…”
Section: Geriatrisk Vurdering Geriatrisk Vurderingunclassified
“…En omfattende geriatrisk vurdering (CGA) spiller en vigtig rolle i etableringen af en individuelt tilpasset behandlingsplan for den aeldre patient med kraeft [22]. Flere studier har vist, at størstedelen af aeldre patienter, der modtager strålebehandling, er skrøbelige, men betydningen af CGA hos denne patientgruppe er fortsat ikke fuldstaendigt afklaret [23,24]. En CGA kan formentlig bidrage til individuelle hensyn til gennemførelse af…”
Section: Geriatrisk Vurdering Geriatrisk Vurderingunclassified
“…7,[20][21][22][23] Data indicate that patients with localized NSCLC treated with SBRT die of other causes than lung cancer, one of which may be thromboembolism. [24][25][26] SBRT might further increase the risk of VTE in this group of patients. Thus, the aim of this study was to investigate the impact of SBRT on thrombin generation and platelet aggregation in patients with localized NSCLC.…”
Section: Introductionmentioning
confidence: 96%
“… 7 , 20 23 Data indicate that patients with localized NSCLC treated with SBRT die of other causes than lung cancer, one of which may be thromboembolism. 24 26 …”
Section: Introductionmentioning
confidence: 99%
“…Several papers in this Special Issue focused on the prediction of outcomes in older adults with cancer. Kirkelund Bentsen et al showed that the combination of G8 with handgrip strength improved the prediction of overall survival in patients with non-small cell lung cancer [ 3 ]. Similarly, Feliu et al showed that geriatric assessment can predict unplanned hospitalizations in patients undergoing chemotherapy [ 4 ].…”
mentioning
confidence: 99%